2006
DOI: 10.1007/s11258-005-9056-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of wetland vegetation in the Bulgarian high mountains, main gradients and context-dependence of the pH role

Abstract: We fill a gap in understanding wetland vegetation diversity and relationship with environmental determinants in Bulgarian high mountains. A total of 615 phytosociological samples were taken from springs, mires, wet meadows and tall-forb habitats throughout Bulgaria, of which 234 releve´s are from mire and spring vegetation above timberline. The vegetation was classified by TWINSPAN and the resulting vegetation types were reproduced by the formal definitions using the combination of Cocktail species groups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 47 publications
3
68
1
Order By: Relevance
“…2+ , pH and EC could be used to characterize the acidity-alkalinity gradient, which had a primary role in segregation of the plant communities and of these pH also explains the largest part of the vegetation variation (Hájková et al 2006). Other important gradients for the wet meadow vegetation, beside the acidity are humidity and nutrient gradient (Tables 2, 4).…”
Section: Floristic Gradients and Environmental Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…2+ , pH and EC could be used to characterize the acidity-alkalinity gradient, which had a primary role in segregation of the plant communities and of these pH also explains the largest part of the vegetation variation (Hájková et al 2006). Other important gradients for the wet meadow vegetation, beside the acidity are humidity and nutrient gradient (Tables 2, 4).…”
Section: Floristic Gradients and Environmental Parametersmentioning
confidence: 99%
“…Wet meadows and other similar wetland-types have been the object of several studies throughout Europe in the last years (Hájek & Hájková 2004;Havlová et al 2004;Hölzel & Otte 2004;Hrivnák 2004;Botta-Dukát et al 2005;Grootjans et al 2005;Stančić 2005;Zelnik 2005a,b;Hájková et al 2006;Havlová 2006), since the threat to the biodiversity of these ecosystems is still increasing and numerous sites have been destroyed, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, only half of the relevés were assigned to the associations by the formal definitions. This rate is somewhat higher than in several other studies that applied national definitions to the regional mire data sets Hájková et al 2006;Dítě et al 2007). Kuželová & Chytrý (2004) demonstrated changes in interspecific associations (i.e.…”
Section: Discussionmentioning
confidence: 55%
“…We accepted a characterisation of each vegetation type by the formal definition using the combination of defined species groups created by the Cocktail method (see Bruelheide 2000;Kočí et al 2003;Hájková et al 2006;Chytrý 2007) with the statistical tendency of joint occurrences in vegetation, calculated by the phi-coefficient (Chytrý et al 2002). In the first step, we used the defined groups of species with the statistical tendency of joint occurrences in vegetation (called sociological species groups further in the text) and formal definitions of mire associations created based on 4117 phytosociological relevés from the West Carpathians ; see Appendix 1 and 2).…”
Section: Data Processingmentioning
confidence: 99%
“…From a historical perspective, the relevé method of community classification (Mueller-Dombois and Ellenberg 1974) has strongly influenced notions of plot size, and variations on this approach are still widely used (Peet 1981;Wells 1996;Dierssen and Dierssen 2005;Hajkova et al 2006). Mueller-Dombois and Ellenberg (1974) indicated that the sample area should be large enough to contain all of the species belonging to a plant community and should be relatively uniform in total plant cover.…”
Section: Defining and Locating Sampling Units In The Fieldmentioning
confidence: 99%